Are informed policies in place to promote safe and usable EHRs? A cross-industry comparison. (19th February 2017) - Savage, Erica L; Fairbanks, Rollin J; Ratwani, Raj M
Abstract: Objective: Despite federal policies put in place by the Office of the National Coordinator (ONC) to promote safe and usable electronic health record (EHR) products, the usability of EHRs continues to frustrate providers and have patient safety implications. This study sought to compare government policies on usability and safety, and methods of examining compliance to those policies, across 3 federal agencies: the ONC and EHRs, the Federal Aviation Administration (FAA) and avionics, and the Food and Drug Administration (FDA) and medical devices. Our goal was to identify whether differences in policies exist and, if they do exist, how policies and enforcement mechanisms from other industries might be applied to optimize EHR usability. Method: We performed a qualitative study using publicly available governing documents to examine similarities and differences in usability and safety policies across agencies. Results: The policy review and analysis revealed several consistencies within each agency's usability policies. Critical differences emerged in the usability standards and policy enforcement mechanisms utilized by the 3 agencies. The FAA and FDA look at evidence of usability processes and are more prescriptive when it comes to testing final products as compared to the ONC, which relies on attestation and is less prescriptive. Discussion: A comparison of usability policies across industries illustrates key differences between the ONC and other federal agencies. These differences could be contributing to the usability challenges associated with EHRs. Conclusion: Our analysis highlights important areas of usability and safety policy from other industries that can better inform ONC policies on EHRs.